Study Habits and Attitudes of Secondary School Students in India - Mishra, Savita (International Journal of Social Learning (IJSL), 2022)
Study habits and attitudes are intended to elicit and guide one’s cognitive processes through appropriate study hours and use them at the appropriate time and places during learning. The study aims to assess secondary school students' study habits and attitudes concerning gender, caste and parental occupation, and educational and income levels. A sample of 150 secondary school students was selected on a simple random basis from Gangtok, Sikkim. The findings of the study were that gender, socioeconomic status, Parental education, Parental occupation, and parental income does not make any difference in the study habit and attitude of both boys and girls, but caste plays a role in the study habits and attitude of both boys and girls.